The Efficacy of Oral Antioxidant on Glycemic Index and Lipid Profile in Patients With Type II Diabetes Mellitus: A Systematic Review - Ni Made Wini Jayesthiwi Wanami Putri; Sagung Intan Saraswati; Komang Vika Nariswari Ratna Kinasih; Ida Ayu Santhi Pertiwi Manuaba (Eduvest - Journal of Universal Studies, 2026)
Background: Type 2 diabetes is caused by insulin resistance or insufficient insulin for glucose metabolism, with its pathogenesis linked to free radical exposure. High free radical concentrations and low antioxidant levels increase the risk of complications in diabetes mellitus. Despite this, antioxidant supplementation in diabetic patients remains uncommon. This systematic review explores the efficacy of antioxidant supplementation on therapeutic outcomes in type II diabetes mellitus patients. Methods: A literature search was conducted from January to February 2024 across three databases: PubMed, Science Direct, and Google Scholar. Inclusion criteria focused on adult patients aged >18 years diagnosed with type II diabetes mellitus, randomized controlled trials (RCTs), studies on antioxidant supplementation (excluding non-supplement forms), and studies covering glycemic indices (FPG, PPG, 2hPG, HbA1c) and lipid profiles (LDL, HDL, cholesterol, TG) published from 2014 to 2024 in English or Indonesian. Pediatrics and in vitro/in vivo studies were excluded. Results: The bias risk was assessed using the 2020 PRISMA guidelines. Six journals met the inclusion criteria. The review found that supplementation with turmeric, ellagic acid, Nigella sativa, zinc, vitamins C, and E significantly affected glucose and lipid levels in type II diabetes mellitus patients. However, selenium supplementation showed inconsistent results regarding blood glucose levels and lipid profiles, indicating the need for further investigation. Conclusion: Supplementation with turmeric, ellagic acid, Nigella sativa, zinc, vitamins C, and E is effective in controlling blood glucose levels and improving lipid profiles in type II diabetes mellitus patients.